Pengembangan Inovasi Teknologi Pengolahan Produk Fungsional Makaroni Ikan Gabus (Channa Striata) Di Kelurahan Pangkalan Kerinci Kota Kabupaten Pelalawan - Rahman Karnila; Mirna Liza; Edison Edison; Sumarto Sumarto (Unri Conference Series: Community Engagement, 2021)
This activity aims to develop technological innovations for processing functional products on snakehead fish macaroni as a new variant of the business during the COVID-19 pandemic in the "Bunda Nabila" Pelalawan Regency. The method of activity is carried out through counseling and direct training in the processing of macaroni products with the addition of 1% fish flour. The results of the service activities obtained that snakehead fish macaroni can provide a new variant with a neat, intact, bright yellowish color appearance. The taste of the macaroni becomes more savory with fish. The aroma has a slight savory aroma of fish, with the texture of the macaroni being crunchy and crumbly when eat. The results of consumer assessments of functional macaroni with the addition of 1% snakehead fish flour have the highest consumer acceptance reaching 98% with the "like and very like" category. The sensory factors of taste and crunch determine the success of the new variant in the production of functional macaroni with the fortification of snakehead fish flour with a distinctive, savory, and delicious taste. The nutritional content of snakehead fish flour is 6.92% water content, 85.35% protein, 2.78% fat, 2.92% ash, and 2.03% carbohydrates. The characteristics of snakehead fish macaroni are as follows: moisture of 7.32%, protein 19.63%, fat 6.19%, ash 3.38%, and carbohydrates 63.48%. The achievements of service activities meet the 100% target, including training activities, and the products produced have good sensory and nutritional characteristics.